The Digitalisasi dan Legalitas Usaha terhadap Penjualan Produk di Desa Cisantana - Mahadianto, Moh Yudi; Yana, Enceng; Aripin, Rifky Akbar; Munandar, Irwansyah; Maulady, Parah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Digitalization of marketing in Micro, Small and Medium Enterprises (MSMEs) is one of the important factors in marketing in the digital era. But in fact, many MSME business actors still do not have insight or understanding regarding digitalization marketing for their product marketing media. This problem is still a study of the problems of MSME business actors in Cisantana village, which results in the scope of marketing of MSME products in this village being very narrow. In addition, the lack of understanding regarding the importance of business legality for MSMEs is also still a major problem for MSMEs in developing their businesses. This can be overcome by socialization and training to provide understanding to business actors regarding the importance of marketing digitalization and business legality. With this activity, it is hoped that MSME business actors can be more productive in developing their businesses, especially in the field of product marketing and MSME actors can be more aware of the importance of business actors completing their business legality. The output of this service activity is that MSMEs are more developed by following the times, namely marketing through digital marketing and having complete licensing.